Recent Applications of Interfacial Exciplex as Ideal Host of Power-Efficient OLEDs - Zhang, Baohua; Xie, Zhiyuan (Frontiers in Chemistry, 2019)
Currently, a hot topic is focused on exploring the applications of intermolecular donor-acceptor exciplex couple as host of OLEDs with phosphorescence, thermally activated delayed fluorescence (TADF) or fluorescence emitter as dopant. Compared to other host strategies, interfacial exciplex have the advantages in various aspects, such as barrier-free charge injection, unimpeded charge transport, energy-saving direct exciton formation process at the “Well”-like heterojunction interface region. Most importantly, due to very fast and efficient reverse intersystem-crossing (RISC) process, such host is capable of regulating singlet/triplet exciton populations in itself and also in the dopant emitters both under photoluminescent (PL) and electroluminescent (EL) driving conditions. In this mini-review, we will briefly summarize and comment on recent applications of this ideal host in OLEDs (including both thermal-evaporation OLEDs and solution-processed OLEDs) with diverse emitters, e.g. fluorescence, phosphorescence, delayed fluorescence or others. Special attention is concentrated on illustration the peculiar achievement of high overall EL performance with superiorities of low driving voltages, slow roll-off rate, high power efficiencies and satisfied device lifetime using this host strategy, which is concluded by personal perspectives toward the relevant next-step work.